Ion-Exchange Resin Catalysed Esterification of Isopropanol with Chloroacetic Acids - Aboul-Magd, A.S.; Kamal, F.H.; Ebaid, A.R.; Barakat, A.M. (Asian Journal of Chemistry, 2010)
Studies have been made on the kinetics of the esterification of isopropanol with chloroacetic acids (mono-, di- and trichoro acetic acids, using Imac 20Ar as a catalyst. The influence of chloro-substituted acid on the esterification has been investigated. The experimental data was found to befit a second order bimolecular kinetic equation.